Incidence and Factors Associated With Concussion Injuries at the 2011 to 2014 South African Rugby Union Youth Week Tournaments. Issue 5 (September 2016) - Mc Fie, Sarah; Brown, James; Hendricks, Sharief; Posthumus, Michael; Readhead, Clint; Lambert, Mike; September, Alison V.; Viljoen, Wayne
Abstract : Objective: To determine the concussion incidence and to identify factors associated with concussion in South African youth rugby union players. Design: Prospective cohort study. Setting: Injury surveillance was completed at the South African Rugby Union Youth Week tournaments (under-13, under-16, and under-18 age groups). Participants: South African youth rugby union players. A total of 7216 players participated in 531 matches between 2011 and 2014. Interventions: None. Main Outcome Measures: Concussion incidence was calculated per 1000 player-match-hours with 95% CIs. Poisson regression was used to calculate the incidence rate ratio (IRR) between factors (age, time period, playing position, and activity at the time of concussion) potentially associated with concussions. Results: The concussion incidence was 6.8/1000 player-match-hours (95% CI, 5.5-8.1) across all age groups. Under-13s (IRR, 1.5; P = 0.09) and under-16s (IRR, 1.7; P = 0.03) had higher concussion incidence rates than the under-18 age group. The incidence was higher in the third (IRR, 2.1; P = 0.04) and fourth (IRR, 2.5; P = 0.01) quarters of matches compared with the first quarter. Sixty-two percent of concussions occurred in the tackle situation. The tackler had a 4-fold greater concussion rate (IRR, 4.3; P < 0.001) compared with the ball carrier. The hooker and loose forwards had higher incidence rates than several other player positions ( P < 0.05). Conclusions: The reported concussion incidence falls within the broad range previously reported in youth rugby. The evidence highlighted in this study may contribute to targeted concussion prevention strategies and provide a baseline against which the effectiveness of future interventions can be measured.